Neocolonial Fictions of the Global Cold War - Keith, Joseph; Belletto, Steven (Book collections on Project MUSE., 2019)
"This collection brings together some of the best scholars writing on the U.S. literatures of the global Cold War. The introduction argues that the concept of "neocolonialism" is a significant though neglected theoretical and historical framework through which to recast postwar literature because it helps us see the Cold War as a global conflict, not merely in terms of the East/West divide between Soviet-style totalitarianism and U.S.-style democratic freedom, but in terms of the North/South divide, between nations rich and poor, mostly white and mostly not. Neocolonial fictions draws together and puts into conversation two broad critical developments: the transnational turn in American Studies and the global turn in Cold War cultural and literary studies. While these fields are implicitly linked insofar as one cannot talk about the Cold War U.S. without gesturing toward the rest of the world, this collection is the first to place these fields in explicit conversation with each other. In doing so, this volume contributes to both fields, but also reframes them in significant ways by reorienting Cold War U.S. literatures within a transnational frame and by providing a much needed historical and political contextualization for the emergence and investments of transnational American literary studies"--